The Effect Of Purple Sweet Potato Flour Substitution On The Quality Of Blooming Steamed Sponge - Rambe, Siti Afifah; Gusnita, Wiwik (Universitas Negeri Padang, 2022)
Sponge steamed blooms are cakes made from eggs and sugar which are beaten until they are white and fluffy, then flour and other ingredients are added which are cooked by steaming. The characteristic feature of blooming steamed sponge is that it has a bowl-like shape, split into four parts and has a color at the top of the crack. The purpose of this study was to analyze the effect of substitution of purple sweet potato flour as much as 10%, 20%, 30% on the quality of the blooming steamed sponge. This type of research is a pure experimental study with a completely randomized design (CRD) method. The data collection technique of this research was carried out by organoleptic tests given to 5 expert panelists, namely lecturers of Family Welfare Sciences, Padang State University. The data analysis technique used was Analysis of Variance (ANOVA) to analyze organoleptic test data. The data that has been obtained is then tabulated in tabular form and analyzed according to the test of each data. Then the data analysis is carried out, if the data obtained by Fcount is greater than Ftable, then it is continued with Duncan's test. It can be concluded that a good percentage is found in the substitution of purple sweet potato flour as much as 10% on the quality of the blooming